COVID-19 symptoms and compliance: The mediating role of fundamental social motives - Liu, Ruoting; Zheng, Xueying; Wang, Ziyu; Zhou, Mingjie; Weng, Jianping; Li, Yan-mei; Chen, Xuefeng (Frontiers in Psychology, 2023)
Abstract Background: Understanding the compliance of infected individuals and the psychological process underlying compliance during pandemics is important for preventing and controlling the spread of pathogens. Our study investigated whether fundamental social motives mediate the relationship between having infectious disease and compliance. Methods: In an online survey conducted during the severe period of COVID-19 in China, 15758 participants completed self-report questionnaires containing questions on current symptoms and measures of fundamental social motives and compliance. Results: The participants with COVID-19 symptoms had lower levels of compliance than those without symptoms, and their lower compliance was caused by a decrease in disease avoidance and familial motives (i.e., mate retention, kin care (family), kin care (child)). Whereas exclusion concern suppressed the effects of COVID-19 symptoms on compliance, these effects disappeared in the multiple mediation model, while those of disease avoidance and familial motives remained. Conclusions: Our findings highlight the importance of fundamental social motives in guiding norm compliance during pandemics and in developing interventions aimed at reducing the noncompliance with public health measures for potentially infected people.